ผลของโปรแกรมส่งเสริมการบริโภคอาหารลดโซเดียมต่อความรู้ และปริมาณโซเดียมในปัสสาวะของนักศึกษาพยาบาล - บุญศิริ ชลธิชา; เปียซื่อ นพวรรณ; พุธวัฒนะ พรรณวดี; กันตชูเวสศิริ สุรศักดิ์ (Journal of Thailand Nursing and Midwifery Council, 2017)
Objectives: 1) To describe knowledge of sodium consumption and urinary sodium in nursing students, 2) to compare knowledge of sodium consumption at baseline, before, and after the program, 3) to compare urinary sodium at baseline, before, and after the program, and 4) to compare sodium consumption behaviors in nursing students at baseline and after the program. Designs: Quasi-experimental design with one-group self-control. Methodology: Sample included 44 second year nursing students in a nursing institution. The sample participated in the 3-week program promoting food consumption for sodium reduction. Data were collected using demographic questionnaire, questionnaire on knowledge of sodium consumption, food record form, and 12-hour urinary sodium. Data were analyzed using descriptive statistics, Paired t-test, and One-way repeated-measures ANOVA. Results: Results revealed that the sample had knowledge on sodium intake (8.6 + 2.2) at moderate level. Sodium consumption behavior as measured by sodium intake was 3,497.4 + 720.2 mg/day, more than recommendation. Urinary sodium (2,090.9 + 703.7 mg/day) was at high level. After the program, the sample had knowledge (13.9 + 0.8) more than before (10.3 + 2.3) and baseline (p < .001). Urinary sodium (1,764.7 + 605.2 mg/day) was less than before (2,775.2 + 1087.9 mg/day) and baseline (p < .001), Sodium intake (2,131.8 + 519.5 mg/day) was less than baseline with statistical significance (p < .001). Recommendation: Community nurse practitioners and health team could apply the program to promote reduction of sodium intake in nursing students and extend to other populations.